Reversible Splenial Lesion Syndrome and Multisystem Inflammatory Syndrome Findings in a Child with SARS-COV-2 Infection - Gemici, Utku; Güngör, Mesut; Kara, Bulent; Anik, Yonca (Journal of Pediatric Neurology, 2022)
Reversible splenial lesion syndrome (RESLES) is a transient lesion in the splenium of the corpus callosum. Etiology includes infections, malignancies, drugs, metabolic disorders, trauma, etc. We reported radiological features of a child with RESLES and multisystem inflammatory syndrome (MIS-C) with severe acute respiratory syndrome COVID-19 (SARS-CoV-2) infection in a 11-year-old boy. Diagnosis of SARS COV-2 infection was based on the detection of antiSARS-CoV-2 IgG and IgM in his serum.
Keywords: COVID-19; multisystem inflammatory syndrome; reversible splenial lesion syndrome; cytotoxic lesions of the corpus callosum